Polski przekład dramatu Asji Srnec Todorović Odbrojavanje wobec kategorii ciała i cielesności - Wołek‑San Sebastian, Katarzyna (Przekłady Literatur Słowiańskich, 2015)
Category of ‘the body and corporeality’ in Polish translation of the drama Odbrojavanje (The Countdown) by Asja Srnec Todorović The article discusses the key category of ‘the body and corporeality’ in contemporary Croatian drama and its Polish translation basing on the drama Odbrojavanje (‘The Countdown’) by Asja Srnec Todorović. Odbrojavanje concerns itself with the issue of the sources and the essence of violence, to which the body, as the subject and the object of violence, is connected. Analysis of the Polish translation of the drama allows one to realize how does the ‘experience of the body’ function in different linguistic discourses realized in the text. Discourse identification is inevitable for the categories of the body and corporality to be successfully transferred into the new linguistic space. Key words: the body and corporeality, contemporary Croatian drama, translation